Paleomagnetic constraints on the timing and distribution of Cenozoic rotations in Central and Eastern Anatolia - Gürer, Derya; Van Hinsbergen, Douwe J.J.; Özkaptan, Murat; Creton, Iverna; Koymans, Mathijs R.; Cascella, Antonio; Langereis, Cornelis G. (Copernicus Publications, 2018)
To quantitatively reconstruct the kinematic evolution of Central and Eastern Anatolia within the framework of Neotethyan subduction accommodating Africa-Eurasia convergence, we paleomagnetically assess the timing and amount of vertical axis rotations across the Uluklisla and Sivas regions. We show paleomagnetic results from ∼30 localities identifying a coherent rotation of a SE Anatolian rotating block comprised of the southern Klrisehir Block, the Uluklisla Basin, the Central and Eastern Taurides, and the southern part of the Sivas Basin. Using our new and published results, we compute an apparent polar wander path (APWP) for this block since the Late Cretaceous, showing that it experienced a ∼30-35° counterclockwise vertical axis rotation since the Oligocene time relative to Eurasia. Sediments in the northern Sivas region show clockwise rotations. We use the rotation patterns together with known fault zones to argue that the counterclockwise-rotating domain of south-central Anatolia was bounded by the Savclll Thrust Zone and Deliler-Tecer Fault Zone in the north and by the African-Arabian trench in the south, the western boundary of which is poorly constrained and requires future study. Our new paleomagnetic constraints provide a key ingredient for future kinematic restorations of the Anatolian tectonic collage.
Keywords: Soil Science; Geophysics; Geology; Geochemistry and Petrology; Earth-Surface Processes; Stratigraphy; Palaeontology